Effect Of Lime and Guano To Growth and Yield of Okra Grown in Peat Soil - Berto, Heri; Santoso, Eddy; m, Darussalam (Jurnal Sains Mahasiswa Pertanian, 2019)
The research aimed were to obstain the best dose of interaction between lime and guano on the growth and yield of okra grown on peat soil. The research was carried out at the research garden of the Faculty Agriculture, Tanjungpura University, starting from October until December 2018. The experimental was in factorial design of experiment was on completely randomized design (CRD) consisting of two factors namely lime (a) and guano (b). Lime consist of 3 treatment levels, namely a1 (49 g lime/polybag), a2 (66 g lime/polybag) and a3 (83 g lime/polybag), and guano consist of 3 levels of treatment namely, b1 (45 g guano/polybag), b2 (90 g guano/polybag) dan b3 (135 g guano/polybag), there are 9 treatment combinations with 3 replications and each replication consists of 4 sample plants. The combination of treatments were to is a1b1, a1b2, a1b3, a2b1, a2b2, a2b3, a3b1, a3b2, and a3b3. The variables observed in this study were plant height (cm), root volume (cm3), plant dry weight (g), fruit numbers per plant (fruit), fruit weight per plant (g) and average weight per fruit (g). The results showed that there were no interaction doses between lime and guano was found, but the effective doses were able to increase the growth and yield of okra namely 66 g lime/polybag and 90 g guano/polybag.Keyword : guano, lime, okra, peat soil